On the Behavior of Coupled Shear Walls: Numerical Assessment of Reinforced Concrete Coupling Beam Parameters. (22nd May 2021) - Nofal*, Omar M.; ,; Elsayed, Mostafa; Akl, Adel; Abdel-Mooty, Mohamed
No abstract available